Assessing the Regulatory Impact of Community-Based Forest Management on Ecosystem Sustainability and Community Livelihoods - Sukirno Sukirno (Syura: Journal of Law, 2026)
This study addresses the problem of whether the Community-Based Forest Management (CBFM) program effectively integrates ecosystem conservation with improving the welfare of local communities. Despite its participatory approach, challenges remain in governance, transparency, and policy coordination. The objective of this research is to evaluate the effectiveness of CBFM implementation in achieving ecosystem balance while enhancing community livelihoods. The study employs a qualitative case study design with a descriptive-analytical approach. Data were collected through in-depth interviews, field observations, and documentation to obtain comprehensive insights into program implementation. The findings reveal that CBFM has contributed significantly to increasing vegetation cover, maintaining water resource stability, and reducing illegal logging practices. In addition, the program has improved local incomes, particularly in the Purwokerto area, through diversification of livelihoods based on non-timber forest products and agroforestry systems. However, its effectiveness is constrained by limited participatory governance, unequal benefit distribution, and weak cross-sectoral policy integration. This study contributes to the development of legal and policy frameworks by emphasizing the need for strengthened governance, transparency, and integrated policies to ensure sustainable forest management and equitable community welfare.